Effect of postoperative radiotherapy on survival for surgically managed pT3N0 and pT4aN0 laryngeal cancer: Analysis of the National Cancer Data Base. Issue 12 (9th February 2017) - Graboyes, Evan M.; Zhan, Kevin Y.; Garrett‐Mayer, Elizabeth; Lentsch, Eric J.; Sharma, Anand K.; Day, Terry A.
Abstract : BACKGROUND: The current study was conducted to determine the effect of postoperative radiotherapy (PORT) on overall survival in patients with surgically managed pT3‐T4aN0 laryngeal squamous cell carcinoma (SCC). METHODS: A review of the National Cancer Data Base from 2004 through 2013 was performed. Patients with surgically managed pT3‐4aN0 laryngeal SCC with negative surgical margins were included. Univariable and multivariable Cox regression analyses were used to determine factors associated with survival. RESULTS: A total of 1460 patients were included, 46.2% of whom had pT3N0 disease (674 patients) and 53.8% of whom had pT4aN0 disease (786 patients). Approximately 72.0% of the patients with pT3N0 disease (485 patients) and 50.1% of the patients with pT4aN0 disease (394 patients) received PORT. PORT was not found to be associated with improved overall survival on univariable analysis for patients with pT3N0 disease (hazard ratio [HR], 0.84; 95% confidence interval [95% CI], 0.62‐1.14), but was for patients with pT4aN0 disease (HR, 0.57; 95% CI, 0.45‐0.71). For patients with pT3N0 SCC of the larynx, in a multivariable Cox regression analysis adjusting for age >65 years, severity of comorbidities, larynx subsite, extent of laryngectomy, and number of lymph nodes removed, PORT was not found to be associated with improved survival (adjusted HR, 0.88; 95% CI, 0.64‐1.21). For patients with pT4aN0 disease, the administration of PORT was associated with improved survival on multivariable analysis adjusting for age >65 years, severity of comorbidities, larynx subsite, number of lymph nodes removed, and type of hospital (adjusted HR, 0.58; 95% CI, 0.46‐0.73). CONCLUSIONS: For patients with surgically managed pT3N0 laryngeal SCC with negative margins, PORT does not appear to be associated with improved survival. Despite a survival benefit, nearly 50% of patients with pT4aN0 laryngeal SCC and negative surgical margins do not receive standard‐of‐care PORT. Cancer 2017;123:2248–2257. © 2017 American Cancer Society . Abstract : In a review of the National Cancer Data Base of patients with surgically managed, pT3N0 laryngeal squamous cell carcinoma (SCC) with negative margins, the use of postoperative radiotherapy (PORT) does not appear to be associated with improved survival. Patients with pT4aN0 laryngeal SCC and negative margins have improved survival with PORT, but nearly 50% of patients with pT4aN0 laryngeal SCC do not receive standard‐of‐care PORT.